Protease inhibitors, inflammatory markers, and their association with outcome in dogs with naturally occurring acute pancreatitis. (7th September 2020) - Kuzi, Sharon; Mazaki‐Tovi, Michal; Suchodolski, Jan S.; Rimer, Dar; Lidbury, Jonathan A.; Steiner, Joerg M.; Buono, Agostino; Nivy, Ran; Segev, Gilad; Aroch, Itamar
Abstract: Background: Acute pancreatitis (AP) presumably is associated with pancreatic protease activation, protease inhibitor (PI) depletion, and inflammatory mediator secretion. Objectives: Examine PIs and inflammatory mediator concentrations in dogs with AP and their association with death. Animals: Thirty‐one dogs diagnosed with AP based on clinical signs, ultrasonographic findings, and increased canine pancreatic lipase immunoreactivity (cPLI) and 51 healthy control dogs. Methods: Antithrombin and α2 ‐antiplasmin activity (ATA and α2 AP, respectively) and concentrations of α1 ‐proteinase inhibitor (α1 PI), α2 ‐macroglobulin (α2 MG), C‐reactive protein (CRP), interleukins (ILs)‐2, 6, 8 and tumor necrosis factor‐α (TNF‐α) were prospectively measured. Severity of AP was assessed by clinical severity scoring systems. Results: Mortality rate was 19%. Antithrombin activity was lower ( P = .004) and maximal CRP, IL‐6, and TNF‐α concentrations higher ( P < .04) in the AP group compared to the controls, whereas IL‐2, IL‐8, α1 PI, and α2 AP concentrations did not differ between groups. Serum α2 MG concentration was not reliably detected. Serum cPLI, CRP, and IL‐6 concentrations were significantly and positively correlated. The ATA was lower ( P = .04), and canine acute pancreatitis severity (CAPS) scores higher ( P = .009) in nonsurvivors compared to survivors. Higher CAPS scores were associated ( P < .05) with decreased ATA and increased cPLI, CRP, and IL‐6 concentrations. Conclusions and Clinical Importance: Systemic inflammation in dogs with AP is manifested by increased inflammatory mediator concentrations, correlating with cPLI and CRP concentrations. Hypoantithrombinemia is associated with death. Serum concentrations of α2 AP and α1 PI are less useful prognostic markers. The CAPS score is a useful prognostic marker in dogs with AP.